Analysis of conjugated steroid androgens: Deconjugation, derivatisation and associated issues - Gomes,RL; Meredith,W; Snape,CE; Sephton,MA (Journal of Pharmaceutical and Biomedical Analysis, 2009)
Gas chromatography/mass spectrometry (GC/MS) is the preferred technique for the detection of urinary steroid androgens for drug testing in athletics. Excreted in either the glucuronide or sulfated conjugated form, steroids must first undergo deconjugation followed by derivatisation to render them suitable for GC analysis. Discussed herein are the deconjugation and the derivatisation preparative options. The analytical challenges surrounding these preparatory approaches, in particular the inability to cleave the sulfate moiety have led to a focus on testing protocols that reply on glucuronide conjugates. Other approaches which alleviate the need for deconjugation and derivatisation are also highlighted.